Intranasal delivery of iron chelators and management of central nervous system disease - Cheng, Ruiying; Kim, Jonghan (Frontiers in Pharmacology, 2025)
Brain iron dyshomeostasis plays a critical role in the pathology of multiple central nervous system (CNS) disorders, including neurodegenerative and neuropsychiatric diseases. Iron chelators such as deferoxamine (DFO) and deferiprone (DFP) have demonstrated therapeutic potential in mitigating disease progression in these conditions. However, systemic administration is hindered by poor blood-brain barrier (BBB) permeability, dose-limiting toxicity, and poor patient compliance due to frequent dosing regimens. In recent years, intranasal (IN) drug delivery has emerged as a promising strategy to bypass the BBB, providing a direct nose-to-brain delivery route via olfactory and trigeminal pathways while minimizing systemic exposure. This review provides a comprehensive summary of the current status of iron chelation therapy for CNS disorders with a focus on pharmacokinetics, efficacy, and translational potential of IN administration. While IN DFO has been extensively studied in preclinical models of Alzheimer’s disease and stroke, recent developments have expanded the scope to other chelators such as DFP. We compare traditional systemic routes, including oral and intravenous, with intranasal administration, highlighting their respective advantages and limitations for CNS delivery. With ongoing advances in formulation and delivery technologies, IN iron chelators provide a promising alternative for the treatment of CNS disorders characterized by impaired iron homeostasis in the brain.